Hydroxysafflor Yellow A (HSYA) Improves Learning and Memory in Cerebral Ischemia Reperfusion-Injured Rats via Recovering Synaptic Plasticity in the Hippocampus - Yu, Lu; Duan, Yanhong; Zhao, Zheng; He, Wendi; Xia, Ming; Zhang, Qiujuan; Cao, Xiaohua (Frontiers in Cellular Neuroscience, 2018)
Hydroxysafflor yellow A (HSYA) is the major active chemical component of the safflower plant flower, which is widely used in Chinese medicine for cerebrovascular and cardiovascular disease treatment. Recent studies have demonstrated that HSYA exerts neuroprotective effect on cerebral ischemia, such as neuronal anti-apoptosis, antioxidant activity and oxygen free radical-scavenging. However, whether and how HSYA has a protective effect on cognitive impairment induced by cerebral ischemia reperfusion remains elusive. In the present study, by using the middle cerebral artery occlusion (MCAO) model, we found that 8 mg/kg and 16 mg/kg HSYA administration by common carotid artery (CCA) injection improved impaired cognitive function in Morris water maze (MWM) and passive avoidance tasks, but not 4 mg/kg HSYA treatment, suggesting that HSYA treatment in a certain concentration can improve cognitive impairment in MCAO rats. Furthermore, we found that 8 mg/kg HSYA treatment rescued the impaired long-term potentiation (LTP) in hippocampus of MCAO rats. Taken together, these results for the first time demonstrate that HSYA has the capacity to protect cognitive function and synaptic plasticity against cerebral ischemia-reperfusion injury, and provide a new insight that HSYA may be a promising alternative for recovery of cognitive dysfunction after brain ischemic injury.